Analysis of Fresh Cow Milk Income in Pujon Sub-District Malang Regency East Java - Soeyatno, Rahmah Farahdita (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Pujon Sub-district is one of the largest milk production centers in Malang Regency, East Java. To achieve sustainability and profitability, dairy farmers in this area must have a clear understanding of their total revenues and production costs. This study aims to analyze the net income of dairy cow farming in Pandesari Village. A quantitative approach with a descriptive method was used in this research. The sampling method applied was purposive sampling, targeting 36 dairy farmers as respondents. Data collection was carried out from September 2012 to January 2013. Both primary and secondary data were used, gathered through interviews, field observations, and documentation. The analysis method applied was income analysis using the Revenue-to-Cost (R/C) ratio. The results indicate that dairy cow farming in Pujon Sub-district is economically feasible and generates moderate profits. A positive R/C ratio shows that every unit of cost incurred by farmers results in a higher amount of revenue. This suggests that the dairy farming business in this area is relatively efficient and has the potential to contribute significantly to farmers' incomes. Therefore, it can be further developed as a primary livelihood source, particularly for small to medium-scale farmers, with opportunities for improving economic welfare through better management practices.